2010
DOI: 10.4028/www.scientific.net/amr.152-153.1726
|View full text |Cite
|
Sign up to set email alerts
|

Alginate-Chitosan Microspheres for Controlled Release of Tea Polyphenol

Abstract: Tea polyphenol loaded alginate-chitosan microspheres were prepared by ionic gelation method for controlling tea polyphenol release by using various combinations of chitosn and Ca2+ as cation and alginate as anion.Scanning electron microscopy were used to investigate the surface characteristics of tea polyphenol loaded microspheres. These microencapsulated beads were evaluated as a pH-sensitive system for delivery of tea polyphenol. The main advantage of this system is that all procedures used were performed in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 14 publications
1
2
0
Order By: Relevance
“…Among investigated samples, the ACP10 nanoparticles were separated well, and their shape is nearly spherical. The morphology of the ACP nanoparticles in this study defers significantly with that of the tea polyphenol-loaded alginate-chitosan microspheres as reported by Wang et al [14,24,26]. The tea polyphenol-4000 3800 3600 3400 3200 3000 2800 1800 1600 1400 1200 1000 800 600 International Journal of Polymer Science loaded alginate-chitosan microspheres have a uniform porous structure with ridges.…”
Section: 2supporting
confidence: 81%
See 2 more Smart Citations
“…Among investigated samples, the ACP10 nanoparticles were separated well, and their shape is nearly spherical. The morphology of the ACP nanoparticles in this study defers significantly with that of the tea polyphenol-loaded alginate-chitosan microspheres as reported by Wang et al [14,24,26]. The tea polyphenol-4000 3800 3600 3400 3200 3000 2800 1800 1600 1400 1200 1000 800 600 International Journal of Polymer Science loaded alginate-chitosan microspheres have a uniform porous structure with ridges.…”
Section: 2supporting
confidence: 81%
“…Radoslava et al synthesized an alginate/chitosan/polyphenol composite which had a significantly better diffusion coefficient than alginate/inulin composite [13]. Wang et al studied the morphology, structure, and kinetics of polyphenol released from the alginate/chitosan/polyphenol [14]. Experimental results showed that in pH 7.4 solution, the polyphenol release process was better than that in pH 1.2 solution.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Microspheres loaded with Ch and Na-Alg, as well as polyphenols extracted from Camelia sinensis L., underwent an in vitro release test. It was found that, after 6 h of exposure to an alkaline medium (pH 7.4), they released over 90% of the extract, whereas exposure to an acidic medium with pH 1.2 resulted in insignificant release [86]. In a different study, the release of Viola odorata L. extract from Ch and Na-Alg microcapsules occurred in two phases in both acidic (pH 1.5) and alkaline (pH 7) environments.…”
Section: Analysis Of the In Vitro Extract Releasementioning
confidence: 95%